Peran Madrasah Diniyah dalam Peningkatan Penguasaan Ilmu Agama Islam dan Pembentukan Kepribadian Islam - Cacang Cacang; Siti Qomariyah; Ridwan Hermawan; Nawil Hadad (Reflection : Islamic Education Journal, 2025)
The moral crisis and low religious understanding among the younger generation pose a major challenge in shaping national character based on Islamic values. This phenomenon is increasingly complex amidst the rapid flow of globalization and technological advances that have led to individualistic, materialistic lifestyles far from the principles of Islamic law. In this context, religious education plays a central role as a moral and spiritual bulwark. This study aims to determine the role of Madrasah Diniyah (Islamic religious schools) in improving the mastery of Islamic religious knowledge and shaping the Islamic personality (syakhsiyah Islamiyyah) of students. This study uses a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation at one of the Madrasah diniyah. The focus of the study is directed at the learning process covering the Qur'an, aqidah, fiqh, and morals, and how this process contributes to the formation of Islamic character in students. The results show that Madrasah Diniyah plays a strategic and significant role in shaping a generation that not only understands religious knowledge but is also able to implement Islamic values in everyday life. This success is supported by several factors, including the quality of competent and exemplary teachers, a structured and contextual curriculum, and good interpersonal relationships between teachers and students. Furthermore, support from parents and the surrounding community is also crucial in strengthening the internalization of Islamic values. Thus, Islamic schools (madrasah diniyah) can function as a vital partner in the Islamic education system, developing a generation with character, noble morals, and a commitment to Islamic teachings from an early age. These findings reinforce the urgency of strengthening religious educational institutions amidst the challenges of the times.